Defying Maliseet language death : emergent vitalities of language, culture, and identity in Eastern Canada - Perley, Bernard C. (University of Nebraska Press, 2011)
Today, indigenous communities throughout North America are grappling with the dual issues of language loss and revitalization. While many communities are making efforts to bring their traditional languages back through educational programs, for some communities these efforts are not enough or have come too late to stem the tide of language death, which occurs when there are no remaining fluent speakers and the language is no longer used in regular communication. The Maliseet language, as spoken in the Tobique First Nation of New Brunswick, Canada, is one such endangered language that will either be revitalized and survive or will die off. Defying Maliseet Language Death is an ethnographic study by Bernard C. Perley, a member of this First Nation, that examines the role of the Maliseet language and its survival in Maliseet identity processes. Perley examines what is being done to keep the Maliseet language alive, who is actively involved in these processes, and how these two factors combine to promote Maliseet language survival. He also explores questions of identity, asking the important question: “If Maliseet is no longer spoken, are we still Maliseet?” This timely volume joins the dual issues of language survival and indigenous identity to present a unique perspective on the place of language within culture.